(Mis-)Recognition of the Socially Accepted Role in Communicative Rituals: A Study of Adolescents with Hearing Loss in School Life - Kim Sune Jepsen; Steen Bengtsson; Inge Kryger Pedersen (Scandinavian Journal of Disability Research)
Standardised medical treatments for children with hearing loss often provide good individual auditory–oral skills, but some research reports more widespread psychosocial difficulties. This raises unresolved questions about the possible sociological explanations for diverging outcomes. In this study, we adopt a micro-sociological approach to demonstrate how successful participation in ritual everyday life relates to active role-taking and role-making, where adolescents can follow along and acquire social acceptance. We explore how 15 adolescents with hearing loss participated in play and peer conversation, comparing students’ experiences from mainstream schools to their experiences from a specialised boarding school in Denmark. A key finding is that mainstream schools involved different degrees of entrapment through a constraining form of role-taking. The specialised boarding school creates space for active role-making through diverse activity opportunities, close relationships, and attentive forms of communication. We discuss the implications for school life.